Comparative Closed Vessel Firing-Ballistic Parameters Evaluation for Development of Base Bleed Composite Solid Propellant - Mukhtar, A.; Nasir, H. (Engineering, Technology & Applied Science Research, 2018)
Closed vessel test (CVT) is widely used for the measurement and comparison of ballistic and energetic properties of propellants by the ignition of a specific sample mass in a closed high-pressure vessel. In our research, comparative CVTs were performed in a vessel, where an internationally accepted composite propellant base bleed grain sample served as a reference (Ref) for recording the standard values of the under investigation propellant composition, in relation to which newly developed samples were characterized. These comparative CVT experiments were performed under chamber volume of 100cm3, sample mass of 10g for all samples and identical ignition system having 1.5g igniter bag of gunpowder. We used closed vessel with working pressure limit of 5000 bars for recording the ballistic parameters of various composite solid propellant samples with reference to a standard sample. It was found that the Ref sample at 50% propellant loading recorded mean maximum pressure (Pm) of 1040 bars in complete combustion time (tPm) of 120ms and vivacity of 0.038 (1/bar∙s). The measured mean Pm was taken as relative force (%) and measured mean vivacity was taken as relative vivacity (%). This data has been used to tune and study the ballistic parameters to develop Ammonium perchlorate (AP) and hydroxyl-terminated polybutadiene (HTPB) based composite solid propellant (CSP) base bleed grain for artillery projectile.